Starting a new anti‐seizure medication in drug‐resistant epilepsy: Add‐on or substitute?. (25th November 2020) - Janmohamed, Mubeen; Lawn, Nicholas; Spilsbury, Katrina; Chan, Josephine; Dunne, John
Abstract: Objectives: Randomized studies in drug‐resistant epilepsy (DRE) typically involve addition of a new anti‐seizure medication (ASM). However, in clinical practice, if the patient is already taking multiple ASMs, then substitution of one of the current ASMs commonly occurs, despite little evidence supporting this approach. Methods: Longitudinal prospective study of seizure outcome after commencing a previously untried ASM in patients with DRE. Multivariable time‐to‐event and logistic regression models were used to evaluate outcomes by whether the new ASM was introduced by addition or substitution. Results: A total of 816 ASM changes in 436 adult patients with DRE between 2010 and 2018 were analyzed. The new ASM was added on 407 (50.1%) occasions and substituted on 409 (49.9%). Mean patient follow‐up was 3.2 years. Substitution was more likely if the new ASM was enzyme‐inducing or in patients with a greater number of concurrent ASMs. ASM add‐on was more likely if a γ‐aminobutyric acid (GABA) agonist was introduced or if the patient had previously trialed a higher number of ASMs. The rate of discontinuation due to lack of tolerability was similar between the add‐on and substitution groups. No difference between the add‐on and substitution ASM introduction strategies was observed for the primary outcome of ≥50% seizure reduction at 12 months. Significance: Adding or substituting a new ASM in DRE has the same influence on seizure outcomes. The findings confirm that ASM alterations in DRE can be individualized according to concurrent ASM therapy and patient characteristics.